R&D; Spillovers and the Case for Industrial Policy in an Open Economy. - Leahy, D; Neary, J (Centre for Economic Performance, LSE, 1997)
In this paper we consider the case for subsidies towards firms which generate R&D; spillovers in open economies. We show that many expected results are overturned in the presence of strategic behaviour by firms. Local R&D; spillovers to other domestic firms may justify an R&D; tax rather than a subsidy; R&D; cooperation by local firms over-internalises the externality and also justifies an R&D; tax; and international spillovers which benefit foreign firms may justify a subsidy, even though the government cares only about the profits of home firms.